2017
DOI: 10.1038/ncomms14812
|View full text |Cite
|
Sign up to set email alerts
|

Winter temperatures limit population growth rate of a migratory songbird

Abstract: Understanding the factors that limit and regulate wildlife populations requires insight into demographic and environmental processes acting throughout the annual cycle. Here, we combine multi-year tracking data of individual birds with a 26-year demographic study of a migratory songbird to evaluate the relative effects of density and weather at the breeding and wintering grounds on population growth rate. Our results reveal clear support for opposing forces of winter temperature and breeding density driving po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 50 publications
(71 reference statements)
1
67
1
Order By: Relevance
“…Between 1987 and 2015, the average (apparent) first‐year survival probability was 10.1% (range = 4.4–18.5%; Woodworth et al. ). We excluded juveniles born in 2004 from our recruitment analyses because population monitoring was interrupted from 2005–2007 and recruitment was unknown.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Between 1987 and 2015, the average (apparent) first‐year survival probability was 10.1% (range = 4.4–18.5%; Woodworth et al. ). We excluded juveniles born in 2004 from our recruitment analyses because population monitoring was interrupted from 2005–2007 and recruitment was unknown.…”
Section: Methodsmentioning
confidence: 99%
“…), Savannah sparrows have been declining on Kent Island since the early 2000's (Woodworth et al. ). Prior to 2016, per capita female fecundity was also declining on Kent Island (Woodworth et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies on the annual survival of migratory birds have found that survival largely depends either on factors that affect the breeding Robinson et al 2010;Blomberg et al 2013) or wintering grounds (Peach et al 1991;Baillie and Peach 1992;Leyrer et al 2013;Salewski et al 2013;Woodworth et al 2017). Nevertheless, a growing number of studies suggest that conditions encountered during migration may also be important for some species (Stokke et al 2005;Newton 2006;Bayly et al 2011), with a few studies providing evidence that mortality during migration may be higher than that experienced at the stationary stages (Ward et al 1997;Sillett and Holmes 2002;Klaassen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As such, changes in weather parameters may occur at the wintering or breeding grounds, as well as at stopover sites (Halupka et al 2008;Zwarts et al 2009;García-Mozo et al 2011). Large-scale climatic changes may also cause weather anomalies along the migratory routes (Tøttrup et al 2012) that may affect the survival or population dynamics of various bird species (Sanderson et al 2006;Ockendon et al 2014;Inger et al 2015;Jansen et al 2015;Woodworth et al 2017).…”
Section: Introductionmentioning
confidence: 99%